Pengaruh Bahasa Gaul Gen Z Terhadap Penggunaan Bahasa Indonesia Baku di Media Sosial Tiktok - Wulansari, Rini; Octaviana, Nadyla Shafa; Nisrina, Ade; Wardhani, Novita Sari; Julaika, Dila Rahma; anhar, Anhar (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to analyze the effect of TikTok usage on the language habits of Generation Z in Indonesia. The background of this study stems from the widespread use of slang that has rapidly developed through social media, particularly TikTok, which has slowly shifted the use of standard Indonesian in everyday communication. This study uses a qualitative approach with an exploratory case study design. Data were collected through a survey of 63 active TikTok users and analyzed using descriptive analysis techniques through the stages of data reduction, data presentation, and conclusion drawing. The results of the study show that 41% of respondents often and 14% very often use slang such as mager, baper, bestie, gaje, and kepo in daily interactions, exceeding the use of standard Indonesian. The analysis of the findings shows that TikTok plays a significant role in strengthening the spread and normalization of informal language among Gen Z. Although this phenomenon reflects the linguistic creativity and identity of the younger generation, it also raises concerns about their formal language skills. Therefore, this study concludes that there is a need for balanced language education efforts so that Gen Z can use slang contextually without neglecting the accuracy of Indonesian language in formal settings